Are There Common Mechanisms Between the Hutchinson–Gilford Progeria Syndrome and Natural Aging? - Ashapkin, Vasily V.; Kutueva, Lyudmila I.; Kurchashova, Svetlana Y.; Kireev, Igor I. (Frontiers in Genetics, 2019)
Accelerated aging diseases could play a significant role in studies of epigenetic mechanisms of the natural aging. The Hutchinson-Gilford progeria syndrome (HGPS) is caused by mutations of LMNA gene leading to an increased production of a partially processed form of the nuclear fibrillar protein lamin A – progerin. Progerin has been shown to act as a dominant factor that leads to multiple morphological anomalies of cell nuclei and disturbances in heterochromatin organization, mitosis, DNA replication and repair, and gene transcription. Small quantities of progerin appear to be produced in normal wild-type cells of mesenchymal origin and tend to be increased with natural aging. Cardiovascular disorders, similar to those in normally aged atherosclerotic patients, are among the most typical manifestations of progerin-induced accelerated aging. Large quantities of progerin are accumulating in arterial walls of HGPS patients. Progerin was also detected in coronary arteria of non-HGPS individuals, its quantity being increased with age. Multiple epigenetic changes were found in cells of HGPS and other progeroid patients, some of them common to accelerated and natural aging. Recent studies showed that epigenetic changes could play an active role as drivers of both forms of aging. It may be suggested that epigenome senses various aging signals, both natural ones, such as the chronological age, and pathological ones, such as progerin, and translates them into universal molecular hallmarks of aging.